Multi-stakeholder Training and Consultative Workshop for Implementing the Scaling Framework in Small Ruminant Improvement - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (International Livestock Research Institute, 2024)
A multi-stakeholder workshop was held on November 20, 2024, to pave the way for implementing the scaling framework using a cluster approach in Menz-Gera Midir Woreda. A total of 28 participants (10 women) were participated. Background papers elaborate on the scaling framework components, including CBBP, production unit, finishing, marketing, entrepreneurship, and enterprise development in the value chain. Additionally, the workshop reviewed the current status of CBBPs and finishing practices in the Menz-Gera district. Based on the background papers, group work and presentation were done to establish the implementation of the scaling framework in Menz Gera Midir woreda. The challenges and the opportunities were identified, and the roles and responsibilities of the stakeholders were also clearly mapped out. The group work and discussion have laid down a scaling framework following a clustering approach for Sina Amba, Tsehay Sina and Dargegne CBBP village as a nucleus, and includes 11 Kebele sheep keepers as a production units, 10 youth group finishers in the rural and five finisher group in the small towns. Yazerber, a small ruminant marketing enterprise, will be a significant market outlet. The total number of finishers in this model village is planned at 191 and 43 individuals in rural and small towns, respectively. It was concluded that the stakeholders’ engagement, technical backstopping, and robust monitoring and evaluation are underscores for piloting the scaling framework and scaling up the good practices in the other districts and zones in Ethiopia.